Determinants of electricity demand in the industrial and commercial sector in Indonesia - Tasia Sapta, Liliana; Junaidi, Junaidi; Umiyati, Etik (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aims to analyze the development of electricity needs in the two main sectors served by PT PLN (Persero), namely the industrial and commercial sectors. Next, an analysis was carried out of the factors thought to influence electricity demand in the industrial and commercial sectors, namely the variables Average Electricity Tariff for the Industrial Sector, GDP for the industrial sector and Domestic Investment in the industrial sector on Electricity Demand in the Industrial Sector. Then the influence of the variable average electricity tariff for the commercial sector, GRDP in the commercial sector and domestic investment in the commercial sector on the demand for electricity in the commercial sector. The analytical method used is descriptive and quantitative analysis with panel data regression analysis tools using 34 provinces during 2017-2021. The results of the analysis show that there has been development in a positive direction towards electricity demand in the industrial and commercial sectors, however developments in 2020 show negative growth which has resulted in an excess supply of electricity. Then the results of panel data regression analysis in the industrial and commercial sectors show that there is a positive and significant influence from the GRDP and domestic investment variables, while the electricity tariff variable has no significant effect at the 95% degree.